Dynamic alloying of high manganese steel - E. I. Marukovich; S. M. Usherenko; A. A. Andrushevich; O. P. Reut; Javad Yazdani-Cherati (Литьë и металлургия)
The option of creating a composite material based on high manganese steel by the method of dynamic alloying in the superdeep penetration mode by flows of powder particles is considered. The dynamic effect of powdered microparticles on a matrix billet transforms the original cast steel into a composite material and leads to a change in mechanical properties.